Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3389/fmicb.2014.00786
|View full text |Cite
|
Sign up to set email alerts
|

Chemoautotrophic growth of ammonia-oxidizing Thaumarchaeota enriched from a pelagic redox gradient in the Baltic Sea

Abstract: Ammonia-oxidizing archaea (AOA) are an important component of the planktonic community in aquatic habitats, linking nitrogen and carbon cycles through nitrification and carbon fixation. Therefore, measurements of these processes in culture-based experiments can provide insights into their contributions to energy conservation and biomass production by specific AOA. In this study, by enriching AOA from a brackish, oxygen-depleted water-column in the Landsort Deep, central Baltic Sea, we were able to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 67 publications
(109 reference statements)
6
37
0
4
Order By: Relevance
“…Facultative chemolithoautotrophic bacteria like ammonia-oxidizing Nitrospirae or the thiosulfate-reducing Sulfuritalea (Kojima and Fukui, 2011) and the sulfur-oxidizing Sulfuricurvum (Kodama and Watanabe, 2004) were detected in well H-52, as well as chemolithoauotrophic ammonia-oxidizing Thau-marcheota (Berg et al, 2014), which constitute 90 % of total archaeal reads.…”
Section: Biogeochemical Processes Affecting Group 3 Wellsmentioning
confidence: 99%
“…Facultative chemolithoautotrophic bacteria like ammonia-oxidizing Nitrospirae or the thiosulfate-reducing Sulfuritalea (Kojima and Fukui, 2011) and the sulfur-oxidizing Sulfuricurvum (Kodama and Watanabe, 2004) were detected in well H-52, as well as chemolithoauotrophic ammonia-oxidizing Thau-marcheota (Berg et al, 2014), which constitute 90 % of total archaeal reads.…”
Section: Biogeochemical Processes Affecting Group 3 Wellsmentioning
confidence: 99%
“…The colonization of above- and belowground plant tissues by microorganisms from surrounding environments initiates interactions that are essential for plant productivity (1, 2), fitness (3, 4), and disease resistance (57). The drivers of plant microbiome structure and composition and the ways in which plant hosts acquire microorganisms from surrounding microbial species pools therefore have consequences for ecosystem dynamics, biodiversity, and agricultural productivity (811). Recent studies have identified critical associations between host and environmental factors and patterns of microbial community structure on plant compartments such as leaves (e.g., see references 12 and 13) and roots (e.g., see references 6 and 14).…”
Section: Introductionmentioning
confidence: 99%
“…If we make the same assumptions as in our oxygen model (water inflow rate = 0.007 km 3 y −1 ; upstream water is geochemically identical to the water in SLW with NH4+ = 3.3 μmol L −1 ; Table S1), then inflow from upstream adds 2.3 × 10 4 mol NH4+ y −1 , for a total annual ammonium supply of 2.4 × 10 4 mol NH4+ y −1 . The SLW water column ammonium demand is estimated to be as high as 1.3 × 10 6 mol NH4+ y −1 , assuming all chemoautotrophic C-fixation is due to nitrification (2.7 nmol C L −1 d −1 ; Christner et al, 2014) and that the stoichiometry associated with chemoautotrophic nitrification is 10 mol N per mol of C fixed; Berg et al, 2015). Subtracting the demand (1.3 × 10 6 mol NH4+ y −1 ) from the supply (2.4 × 10 4 mol NH4+ y −1 ) leaves an annual ammonium deficit of 1.3 × 10 6 mol NH4+ y −1 .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that rates of chemosynthesis are higher at the sediment water interface (Mikucki et al, 2015); however, here we assume that the rate of carbon fixation was constant with depth over the area of the lake. The O 2 demand was calculated assuming 0.1 moles of carbon fixed for every mole of ammonium oxidized (Berg et al, 2015) and a stoichiometry for complete nitrification of NH4+ to NO3- of 2 mol of O 2 per mol of nitrogen oxidized.…”
Section: Methodsmentioning
confidence: 99%